Purchase intention on energy efficient household appliances - a meta-analysis of the studies based on theory of planned behaviour. (17th November 2022) - Gangakhedkar, Rajesh; Kaur, Jaspreet; Karthik, M.
The purpose of this research is to study the purchase intention (PI) on energy efficient household appliances by making a meta-analytic review of the studies that have applied theory of planned behaviour. Results of 30 studies that met the inclusion criteria have been synthesised in the meta-analysis. A moderator analysis is also made in order to examine the reasons for heterogeneity in the studies. Analysis of publication bias is also made. The findings revealed that all the three variables of TPB have medium to large associations with PI of energy efficient appliances. Attitude was found to have the strongest relationship with r = 0.571, followed by perceived behavioural control with r = 0.465 and subjective norms with r = 0.443. Moderator analysis gave mixed results. This meta-analytic review is the first of its kind in the domain of adoption of energy efficient appliances by households. The study gives valuable insights to policymakers and researchers into the prediction of PI on energy efficient household appliances.